Cationic Perylene Antivirals with Aqueous Solubility for Studies In Vivo - Anna A. Shtro; Anzhelika V. Garshinina; Vera A. Alferova; Polina N. Kamzeeva; Viktor P. Volok; Ekaterina S. Kolpakova; Timofei D. Nikitin; Alexey A. Chistov; Evgeny S. Belyaev; Vladimir A. Korshun; Liubov I. Kozlovskaya; Andrey V. Aralov (MDPI AG, 2022)
Perylene-based compounds are attracting significant attention due to their high broad-spectrum antiviral activity against enveloped viruses. Despite unambiguous results of in vitro studies and high selectivity index, the poor water solubility of these compounds prevented in vivo evaluation of their antiviral properties. In this work, we synthesized a series of compounds with a perylene pharmacophore bearing positively charged substituents to improve the aqueous solubility of this unique type of antivirals. Three types of charged groups were introduced: (1) quaternary morpholinium salts (3a-b); (2) a 2'-O-l-valinyl-uridine hydrochloride residue (8), and (3) a 3-methylbenzothiazolium cation (10). The synthesized compounds were evaluated based both on antiviral properties in vitro (CHIKV, SARS-CoV-2, and IAV) and on solubility in aqueous media. Compound 10 has the greatest aqueous solubility, making it preferable for pre-evaluation by intragastrical administration in a mouse model of lethal influenza pneumonia. The results indicate that the introduction of a positively charged group is a viable strategy for the design of drug candidates with a perylene scaffold for in vivo studies.